Morbidade em saúde bucal autorreferida, hábitos de higiene bucal, uso dos serviços de saúde bucal e impacto na qualidade de vida: Um estudo em uma comunidade quilombola - Barbosa, Danilo Vieira (2023)
Introduction: Epidemiological studies are powerful tools for health planning and can enhance our understanding of the health-disease process. In this context, there has been a recognition of the need to study underprivileged ethnic groups, among them, the quilombola communities. These communities were formed by former slaves who escaped and grouped together in remote areas to avoid recapture. Due to the geographical and social circumstances this population group was embedded in, unequal access to essential services emerged, directly impacting the quality of life of these individuals and their descendants who continued these practices. Objective: To analyze self-reported oral health conditions, oral hygiene habits, utilization of health services, and oral health-related quality of life among quilombola communities in a city in northeastern Brazil.Methodology: This study employed an observational, cross-sectional, quantitative, and descriptive-analytical approach. The study population consisted of individuals aged 18 and above, residing in the "Urban Quilombo of Santa Luzia, PB." The research instrument addressed questions related to socioeconomic characteristics, self-reported oral morbidity, oral hygiene habits, and utilization of oral health services. Oral health-related quality of life was assessed using the OHIP-14 questionnaire. Data analysis was performed using SPSS version 20.0 for Windows. The sample was characterized using relative and absolute frequencies, and to investigate the association between dependent and independent variables, the Pearson chi-square test was utilized. Statistical significance was considered at a p-value of <0.05. Results: The sample consisted of 160 participants, predominantly female (62.5%), with a mean age of 42.73 years, ranging from 18 to 83 years. Most individuals lived with a partner (63.8%), were unemployed (58.1%), had a monthly family income lower than a minimum wage (62.5%), and had up to eight years of education (38.8%). The majority of participants reported brushing their teeth (93.1%), with 83.3% doing so two or more times a day. Regarding toothbrush replacement, 73.1% did so within less than 6 months of use. Non-use of dental floss was reported by 90% of the sample. Toothache in the last 6 months was reported by 38.8%, of which 56.5% described it as severe in intensity. In turn, 18.8% experienced facial/head pain in the last 6 months, with 73.3% reporting severe intensity. In the last year, 51.3% of participants sought some form of dental service, and 68.7% of them were attended to. Concerning the last dental appointment, 77.6% utilized public services. The most cited reason for seeking dental care was toothache or extraction (59.0%). The last dental visit was rated as good or very good by 75% of the quilombolas. The majority of participants (61.3%) evaluated their own oral health as good; however, 92.5% stated the need for some form of dental treatment, with dental prostheses being the most cited reason (30.6%). Quality of life had low impact for 91.3% of the participants. A statistically significant association was found between the impact of quality of life and the frequency of toothbrush replacement (p=0.011), presence of toothache in the last six months (p=0.017), frequency of head/face pain in the last six months (p=0.007), and time since the last dental appointment (p=0.004). Conclusion: The occurrence of toothache, head/face pain, and time elapsed since the last dental appointment impacted the oral health-related quality of life of the participating quilombolas.